Lower Limb Ischemia in Atrial Fibrillation: Unusual Presentation - Yadav, Ashok Kumar; Shrivastav, Vijay Kumar; Bhandari, Rupak; Shah, Mahesh Kumar; Parajuli, Roshan (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Thrombosis and embolism are the common causes of acute arterial occlusion. Thrombosis mostly arises from underlying cardiac disease such as a trial fibrillation while arterial occlusion by embolism. Thus, an ischemic limb can result from acute arterial occlusion. Early proper diagnosis and prompt treatment within critical time by emergency physician at the initial clinical interviewing is important in saving the affected leg and the life, thus, avoiding limb amputation and death. This paper reports a case in which the cause of acute ischemia of limb was proved with some diagnostic tests to be a trial fibrillation.